(untitled) (Orinoquia, 2024)
Knowledge of the genetic conservation of fish species is expanding the understanding of population structures in Colombian megadiversity. Efforts to advance in the identification of families, genera and species of fish remain insufficient to establish the great existing endemism. The environmental characteristics, the species and the genetic studies must be the premise for a panoramic vision, of what is described in the theory that endorses what exists in Colombian rivers. A particular case are the studies carried out on the sabaleta Brycon henni, which leads to an understanding of the genetic component for the implementation of repopulation programs in the corresponding environments, according to their evolutionary participation. The call from this perspective is to increase economic support for the comprehensive study of inland water fish, together with the training of a greater number of professionals, who support and demonstrate the real scenario of joint work in biodiversity conservation.